Performance analysis of multi services on container Docker, LXC, and LXD - Adinda Riztia Putri; Rendy Munadi; Ridha Muldina Negara (Institute of Advanced Engineering and Science, 2020)
The emergence of the container in various cloud platforms from open stack to google cloud platform has marked the industry interest in opting for container as their cloud service solution. However, the cloud users should aware of performance overheads of different virtualization solutions in order to avoid quality of service degradation because different container platforms delivered different performances. This research evaluated how different container platforms (Docker, LXC, and LXD) impacted in running different TCP services and also measured system performance of each container compared to the native system without any container solution based on overall performance metrics. This research focuses on the three most used PaaS: FTP server, web server, and mail server. related to previous works, our evaluation results show that performance could vary between containers. In terms of system performance, LXD shows better performance while server performance result varies depending on what service is being evaluated.